Information needs for cancer screening and associated factors of information-seeking behaviour: a qualitative systematic review - Mingyao Zhou; Yuqing Wu; Dan Wang; Fang Cheng (BMC Public Health)
Abstract Background At present, the participation rate in cancer screening is still not ideal, and the lack of screening information or misunderstanding of information is an important factor hindering cancer screening behaviour. Therefore, a systematic synthesis of information needs related to cancer screening is critical. Methods On July 23, 2024, we searched the Cochrane Library, MEDLINE (Ovid), Embase, EBSCO, PsycINFO, Scopus, ProQuest, PubMed, Web of Science, and CINAHL to collect qualitative or mixed-methods studies on information needs of cancer screening. We also searched for grey literature on OpenGrey and Google websites. Data were synthesised using Sandelowski and Barroso’s framework. A top-down approach was adopted to group and synthesise the encodes and then generate analytical themes. Results A total of 37 studies were included. The results of the analysis of cancer screening-related information needs content, cancer-specific information needs content, requirements and preferences for information, and associated factors of information-seeking behaviour were reported. Based on the event timeline, we summarised the information needs of the screening demand side into four themes. Their information needs focus on disease risk factors, signs and symptoms, the importance of screening, the benefits and harms of screening, the detailed screening process, and screening results and explanations. Regarding cancer-specific information needs content, we summarised the specific information needs of cervical, breast, colorectal, and lung cancer. By referring to relevant concepts in the Comprehensive Model of Information Seeking, we synthesised the requirements and preferences for information according to the themes of editorial tone, communication potential, recommended information channels, and recommended source place. The information-seeking behaviours of the screening demanders are mainly passive attention and active searching. The common factors leading to the passive attention of screening demanders are demographic factors and fear of cancer. The most common reason for them to actively search information is lack of information. Conclusions The list of information needs identified in this review can serve as a reference for health professionals and information service providers before carrying out screening-related work to help the cancer screening participants obtain valuable information.